P208 Impact of Morning Symptoms Experienced by COPD Patients on Exacerbation Risk, Rescue Inhaler Usage and Normal Daily Activities. (19th November 2012) - Small, M; Broomfield, S; Pollard, R; Fermer, S
Abstract : Impact of morning symptoms experienced by COPD patients on exacerbation risk, rescue inhaler usage and normal daily activities Background: Patients consider the impact of COPD on morning activities to be substantial. Evidence of the association of morning symptoms and the impact on the entire day with poor breathing control contributes to the understanding of their importance for managing COPD patients. Objectives: To quantify the impact of morning symptoms experienced by patients receiving inhaled corticosteroid plus long-acting β2 -agonist (ICS/LABA) by association with exacerbation frequency, rescue usage and impact on daily activities. Methods: Data were drawn from a real world study of consulting COPD patients in the USA and Europe in 2011. Results were tested for significance (p<0.05) using Mann-Whitney and negative binomial regressions. Confounders included age, gender, BMI, comorbidities, severity, smoking status and adherence. Results: Of the 3790 patients in the study, 593 were receiving ICS/LABA-only (+/– rescue). Of the 177 patients reported to experience morning symptoms, cough (65.5%) and excess sputum (53.1%) were the most common. Compared with patients without morning symptoms, these patients were associated with higher mean exacerbation frequency in the last 12 months (1.04 vs 0.63 p<0.001), rescue usage per day (0.58 vs 0.46 p=0.025) and daytime impact on a 7-point Likert scale where 7 represents a constant impact (3.61 vs 3.00 p<0.001). Conclusion: Morning symptoms were associated with significantly more impaired breathing control for patients treated with ICS/LABA-only therapy. The association implies morning symptoms are an important indicator when assessing the impact of COPD and their presence suggests that further therapeutic intervention may be necessary.